A new species of Calliaspis Dejean, 1837 (Coleoptera: Chrysomelidae: Cassidinae) from French Guyana - Borowiec, L. (Zootaxa, 2003)
Calliaspis cerdai sp. nov. is described from French Guyana. It is similar to C. surinamensis Borowiec, 2000. Both species are the only members of the genus Calliaspis Dejean with a distinctly bicoloured, red and black, pronotum and elytra. A key to species of Calliaspis is provided.